Analysis of matrix metalloproteinase triple-helical peptidase activity with substrates incorporating fluorogenic L- or D-amino acids. - Lauer-Fields, J; Kele, P; Sui, G; Nagase, H; Leblanc, R; Fields, G (2003)
The consequences of improper regulation of collagen turnover include diseases such as tumor cell metastasis and arthritis. Several fluorogenic triple-helical peptide (fTHP) substrates have been constructed presently to examine collagenolytic behavior. These substrates incorporate L- or D-2-amino-3-(7-methoxy-4-coumaryl)propionic acid (Amp) or L- or D-2-amino-3-(6,7-dimethoxy-4-coumaryl)propionic acid (Adp) as the fluorophore and N-2,4-dinitrophenyl (Dnp) as the quencher. The desired sequences were C6-(Gly-Pro-Hyp)5-Gly-Pro-[Amp/Adp]-Gly-Pro-Gln-Gly approximately Leu-Arg-Gly-Gln-Lys(Dnp)-Gly-Val-Arg-(Gly-Pro-Hyp)5-NH2. All four fTHPs formed stable triple-helices. Matrix metalloproteinase-2 (MMP-2) rates of hydrolysis for all fTHPs were considerably more rapid than corresponding MMP-1 rates. Evaluation of individual kinetic parameters indicated that MMP-2 bound to the fTHPs more efficiently than MMP-1. Comparison to a triple-helical substrate incorporating the same sequence but with a different fluorophore [Lys((7-methoxycoumarin-4-yl)acetyl); Lys(Mca)] demonstrated that the shorter side chain of Amp or Adp was better tolerated by MMP-1 and MMP-2. Adp may well be the fluorophore of choice for fTHPs, as (a) fTHPs incorporating Adp were obtained in significantly higher yields than the Amp-containing fTHPs, (b) Adp has a larger Stokes shift than either Amp or Lys(Mca) and thus has less chance of self-quenching, (c) Adp has a relatively high quantum yield, (d) the Adp/Dnp pair is compatible with multiwell plate reader formats, and (e) MMPs better tolerate Adp than Lys(Mca).